The roles of pleiotrophin in brain injuries: a narrative review of the literature - Yupeng Lei; Ruixi Zhou; Qian Mao; Xia Qiu; Dezhi Mu (Annals of Medicine)
Background Pleiotrophin (PTN), a secreted multifunctional growth factor, is highly expressed in the developing brain. Recently, many studies have indicated that PTN participates in the development of brain and plays a neuroprotection after brain injury, especially promoting neuronal survival and neurite outgrowth, stimulating oligodendrocyte maturation and myelination, modulating neuroinflammation, and so on.Objective However, no reviews comprehensively summarize the roles of PTN in brain injuries. Considering this, this review focuses on the roles and related regulatory pathways of PTN in brain injuries, what is known to date.Methods PubMed and Embase databases have been searched, and related studies are compiled and summarized.Results Our review has found PTN participates in the repairment of brain injuries, including hypoxic-ischemic brain injury, preterm white matter injury, traumatic brain injury, and neurodegenerative diseases, mainly based on animal data and small sample size studies. Besides, PTN interacts with receptors, such as, Z-type protein tyrosine phosphatase receptor and syndecan-3, regulating related pathways in these events.Conclusion It suggests PTN as a promising candidate for the treatment of brain injuries clinically. However, the evidence is early in its development. Further multi-center and large-sample studies are warranted to support our findings and determine the clinical value of PTN for treating brain injuries.